Identification of Bmpr-1b and Bmp15 gene mutations in fat tail sheep - ., Maskur; Arman, Chairussyuhur (Indonesian Animal Sciences Society, 2010)
Fat tail sheep (FTS) is regarded as highly prolific local sheep and have been well adapted under tropical climate of Lombok island. BMPR-1B and BMP15 genes that controll reproductive traits such as ovulation rate and litter size in different type of sheep will be studied as candidate genes for prolific traits in FTS. These genesÂ have been reported by various investigators have different prolificacy mechanism between several breeds of sheep, and it is very likely will occur in FTS. This study was designed to understand different prolificacy mechanism that occurred among breed of sheep. One hundred and forty FTS potential for twin and triplet scattered in Lombok Island, West Nusa Tenggara Province were screened to identify mutation of BMPR-1B and BMP15 genes using Forced PCR-RFLP method. Furthermore, the frequency of allel and genotype caused by mutation was measured in each gene. Results of the study indicated that mutation of FecXG at BMP15 gene resulted in two alleles, namely âwild-typeâ(+) AllelÂ was 111 bp and 30 bp, and mutan allel (G) was 141 bp with frequency of 0.675 and 0.325. The combination of allel at BMP15 gen resulted in two genotipes, namely: ++ (111 bp/111 bp) and G+ (141 bp/111 bp) with frequency of 0.35 dan 0.65 in FTS. Mutation of FecB at BMPR-1B gen resulted in two allel, namely âwild-typeâ(+) Allel was 140 bp, and mutan allel (B) was 110 and 30 bp with frequency of 0.718 and 0.282. The combination of allel at BMPR-1B gen resulted in three genotipes, namely: BB (110 bp/110 bp), B+ (110 bp/140 bp), and ++ (140 bp/140 bp), its frequency was 0.11, 0.35 and 0.54 in FTS, respectively. Key words: Mutation, BMPR-1B, BMP15, Fat Tailed, Sheep